2007
DOI: 10.1007/s00420-007-0203-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biomarkers of occupational exposure to toluene at low levels

Abstract: Taking the non-invasive nature of sampling together, Tol in the end-of-shift spot urine sample appears to be the marker of choice for biological monitoring of occupational exposure to Tol at low levels such as <2 ppm as a geometric mean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 34 publications
(39 reference statements)
3
26
0
Order By: Relevance
“…The correlation of o-CR-U ob was less significant with r=0.20 and p<0.05, whereas BeOH-U ob and BMA-U ob did not correlate significantly (r=0.16 and 0.11, respectively, with p>0.10 for both; Table 3). In the two previous studies, one 10) with toluene exposure at moderate levels (at 10 ppm as GM and at 121 ppm as the maximum) and the other 11) at low levels (at 1.6 ppm as GM and 26.5 ppm as the maximum), Tol-U correlated with TWA toluene concentrations in air not only at moderate levels but at low levels. No Tol-B was examined in the moderate exposure study 10) , but separate studies showed that Tol-B significantly correlates with air-borne toluene at low levels 11) as well as at high levels (the maximum level being 132 ppm) 23 Abbreviations are: BeOH-U, benzyl alcohol in urine; BMA-U, benzylmercapturic acid in urine; o-CR, o-cresol in urine; HA-U, hippuric acid in urine; Tol-U, toluene in urine and Tol-B, toluene in blood.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The correlation of o-CR-U ob was less significant with r=0.20 and p<0.05, whereas BeOH-U ob and BMA-U ob did not correlate significantly (r=0.16 and 0.11, respectively, with p>0.10 for both; Table 3). In the two previous studies, one 10) with toluene exposure at moderate levels (at 10 ppm as GM and at 121 ppm as the maximum) and the other 11) at low levels (at 1.6 ppm as GM and 26.5 ppm as the maximum), Tol-U correlated with TWA toluene concentrations in air not only at moderate levels but at low levels. No Tol-B was examined in the moderate exposure study 10) , but separate studies showed that Tol-B significantly correlates with air-borne toluene at low levels 11) as well as at high levels (the maximum level being 132 ppm) 23 Abbreviations are: BeOH-U, benzyl alcohol in urine; BMA-U, benzylmercapturic acid in urine; o-CR, o-cresol in urine; HA-U, hippuric acid in urine; Tol-U, toluene in urine and Tol-B, toluene in blood.…”
Section: Discussionmentioning
confidence: 76%
“…The survey was conducted on the second half of working weeks following the design as previously described 10,11) . In short, TWA toluene exposure concentration was monitored by use of diffusive samplers 12) which were placed on the working cloth (at the chest pocket level) of each worker for approximately 8 h (i.e., typically from 09:00 to 17:00).…”
Section: Air-borne Toluene Monitoring and Biological Monitoring By Mmentioning
confidence: 99%
See 2 more Smart Citations
“…The use was not limited to occupational health where the method was originally developed [1][2][3][4][5][6] , but also in environmental health fields 7,8) . The method has been applied to analysis for un-metabolized mother chemicals 1,[9][10][11][12] as well as for metabolites after proper automated derivatization of metabolites to increase volatility [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%